Identification of inter- and intra-species variation in cereal grains through geometric morphometric analysis, and its resilience under experimental charring. (October 2017) - Bonhomme, Vincent; Forster, Emily; Wallace, Michael; Stillman, Eleanor; Charles, Michael; Jones, Glynis
Abstract: The application of morphometric analysis in archaeobotany has the potential to refine quantitatively identifications of ancient plant material recovered from archaeological sites, most commonly preserved through charring due to exposure to heat. This paper uses geometric morphometrics, first, to explore variation in grain shape between three domesticated cereal species, einkorn ( Triticum monococcum ), emmer ( Triticum dicoccum ) and barley ( Hordeum vulgare ), both before and after experimental charring at 230 and 260 °C. Results demonstrate that outline analysis reliably reflects known variations in grain shape between species and differences due to charring observed in previous experimental work, and is capable of distinguishing the species, with near-perfect results, both before and after charring. Having established this, the same method was applied to different accessions of the same species, which indicated that three different grain morphotypes of einkorn and two, possibly three, of emmer could be identified in the uncharred material, and that at least two different morphotypes for each species could be distinguished even after charring at temperatures up to 260 °C. This opens up the possibility of tracking evolutionary change in crops, both chronologically and geographically, through morphometric analysis. Highlights: Outline analysis reliably reflects known variations in grain shape between species, and differences due to charring. More subtle differences in grain shape between different populations of the same species can be identified. Evolutionary change in crops could potentially be tracked, chronologically and geographically, through morphometric analysis.